Synthesis of Chlorophyll-Binding Proteins in a Fully Segregated Δycf54 Strain of the Cyanobacterium Synechocystis PCC 6803 - Hollingshead, Sarah; Kopečná, Jana; Armstrong, David R.; Bučinská, Lenka; Jackson, Philip J.; Chen, Guangyu E.; Dickman, Mark J.; Williamson, Michael P.; Sobotka, Roman; Hunter, C. Neil (Frontiers in Plant Science, 2016)
In the chlorophyll (Chl) biosynthesis pathway the formation of protochlorophyllide is catalyzed by Mg-protoporphyrin IX methyl ester (MgPME) cyclase. The Ycf54 protein was recently shown to form a complex with another component of the oxidative cyclase, Sll1214 (CycI), and partial inactivation of the ycf54 gene leads to Chl deficiency in cyanobacteria and plants. The exact function of the Ycf54 is not known, however, and further progress depends on construction and characterization of a mutant cyanobacterial strain with a fully inactivated ycf54 gene. Here, we report the complete deletion of the ycf54 gene in the cyanobacterium Synechocystis 6803; the resulting Δycf54 strain accumulates huge concentrations of the cyclase substrate MgPME together with another pigment, which we identified using nuclear magnetic resonance as 3-formyl MgPME. The detection of a small amount ( 13%) of Chl in the Δycf54 mutant provides clear evidence that the Ycf54 protein is important, but not essential, for activity of the oxidative cyclase. The greatly reduced formation of protochlorophyllide in the Δycf54 strain provided an opportunity to use 35S protein labeling combined with 2D electrophoresis to examine the synthesis of all known Chl-binding protein complexes under drastically restricted de novo Chl biosynthesis. We show that although the Δycf54 strain synthesizes very limited amounts of photosystem I and the CP47 and CP43 subunits of photosystem II (PSII), the synthesis of PSII D1 and D2 subunits and their assembly into the reaction centre (RCII) assembly intermediate were not affected. Furthermore, the levels of other Chl complexes such as cytochrome b6f and the HliD– Chl synthase remained comparable to wild-type. These data demonstrate that the requirement for de novo Chl molecules differs completely for each Chl-binding protein. Chl traffic and recycling in the cyanobacterial cell as well as the function of Ycf54 are discussed.